2011
DOI: 10.2134/agronj2011.0153
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Nitrogen Utilization and Grain Technological Quality in Durum Wheat: I. Nitrogen Translocation and Nitrogen Use Efficiency for Protein

Abstract: Durum wheat (Triticum durum Desf.) is widely cultivated in the Mediterranean area where plants generally suff er from water stress during grain-fi lling period. Th is study was conducted to evaluate the infl uence of N levels and water regimes on N translocation and nitrogen use effi ciency for protein (NUEP) in durum wheat grown under Mediterranean conditions. A 2-yr experiment was performed in southern Italy using four cultivars, two water regimes (irrigated and rainfed) and three N levels (0, 60, and 120 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
30
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 47 publications
9
30
1
Order By: Relevance
“…The lower rainfall recorded in the first growing season induced a shortening of the growing cycle by 20 d (Table 1); this caused a lower N uptake in the first year than in the second year, with a consequently lower N content in the plant both at anthesis and at maturity, as reported by Giuliani et al (2011). This may have caused a decrease in assimilation and grain yield, as already reported by other researchers (Blum, 1998; Ercoli et al, 2008).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The lower rainfall recorded in the first growing season induced a shortening of the growing cycle by 20 d (Table 1); this caused a lower N uptake in the first year than in the second year, with a consequently lower N content in the plant both at anthesis and at maturity, as reported by Giuliani et al (2011). This may have caused a decrease in assimilation and grain yield, as already reported by other researchers (Blum, 1998; Ercoli et al, 2008).…”
Section: Discussionsupporting
confidence: 69%
“…Finally, to look for the relationships among plant N content, N utilization, and grain technological quality, a correlation matrix among quality parameters and plant and grain N content, N translocation, N use efficiency for protein, and its components, previously evaluated in Giuliani et al (2011), is shown in Table 9. Plant N content at anthesis and at maturity were highly positively correlated with all the quality parameters; straw N content at maturity showed high and positive correlations with protein and gluten content, much lower correlations with alveograph indices W and P/L, and no correlation with the gluten index.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this study, RE for the six durum wheat cultivars ranged from 60 to 81%. Finally, it must be emphasized that frequent, sizeable irrigations in our study resulted in rapid biomass production and much greater grain yields than the 2 to 3 Mg ha -1 in the wheat studies with RE <50% (Guarda et al, 2004;Giambalvo et al, 2010;Giuliani et al, 2011a). The high RE and AE was probably due to the fact that sudangrass cover crop removed most of the available soil N, and low soil organic matter (<10 g kg -1 ) means lower N mineralization in these soils.…”
Section: Discussionmentioning
confidence: 63%